Efforts to Improve Mathematics Learning Activities and Outcomes through the STAD Model in Grade VI - Dunan, Hendra (International Journal Of Pedagogical Novelty (IJOPNOV), 2024)
This study aims to improve the mathematics learning outcomes of sixth-grade students at MIN 3 Solok Selatan by using the STAD (Student Teams Achievement Divisions) Cooperative Learning Model. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The research subjects were 20 sixth-grade students at MIN 3 Solok Selatan. Data were collected through tests, observations, and documentation. The results showed that the application of the STAD learning model could improve students' mathematics learning outcomes. This improvement was evident from the students' average scores, which rose from 80 in cycle 1 to 90 in cycle 2. In addition, students' learning activities and motivation also increased.